Intimate Partner Violence and Willingness to Use Pre-Exposure Prophylaxis Among Men Who Have Sex With Men in Chengdu, China. Issue 7 (April 2023) - Guo, Pengyue; Hou, Fengsu; Cao, Wangnan; Guo, Yawei; Wei, Dannuo; Li, Jinghua; Hao, Yuantao
Intimate partner violence (IPV) is common in men who have sex with men (MSM). MSM also face increased risk of human immunodeficiency virus infection. However, it is not known whether IPV experience of MSM in China would affect their attitudes toward pre-exposure prophylaxis (PrEP) use. A cross-sectional study was conducted to explore the associations between different types of IPV and willingness to use PrEP in a sample of 608 MSM from November 2018 to May 2019 in Chengdu, China. Univariate and multivariate logistic regression analyses were used to explore the associations between different types of IPV and willingness to use PrEP. The average age of the participants was 31.8 ± 12.3 years, 48.9% of them were aware of PrEP before this study, and only 7.2% were aware of long-acting injectable PrEP (LAI-PrEP). The overall willingness to use any type of PrEP in the next 6 months was 82.2%. Approximately one third of the participants ( n = 198) had experienced at least one type of IPV. We found that experience of sexual perpetration was negatively associated with the willingness to use on-demand PrEP (adjusted odds ratio [ORa] = 0.33, 95% CI = 0.16–0.67) and the overall willingness to use any type of PrEP (ORa = 0.31, 95% CI = 0.15–0.64). The willingness to use LAI-PrEP also had negative associations with any type of monitoring IPV (ORa = 0.58, 95% CI = 0.38–0.91), controlling victimization (ORa = 0.41, 95% CI = 0.21–0.82), and emotional victimization (ORa = 0.58, 95% CI = 0.35–0.97). The findings of this study demonstrate that IPV experiences are negatively associated with willingness to use PrEP among MSM, suggesting that PrEP promotion programs should consider IPV screening and develop explicit intervention strategies for both perpetrators and victims.